Pengaruh Kepemimpinan Kepala Madrasah terhadap Kinerja Guru serta Dampaknya pada Kualitas Pembelajaran di Madrasah Ibtidaiyah Swasta - Annisa Ersa Fatimah; Sehan Rifky Arfanaldy (Tarunateach: Journal of Elementary School, 2026)
This study aims to analyze the influence of madrasah head leadership on teacher performance and its implications on the quality of learning in Private Madrasah Ibtidaiyah, Jalaksana District, Kuningan Regency. This study uses a quantitative approach with an explanatory research design. Data were collected through a Likert scale questionnaire to 92 selected teachers using the proportionate stratified random sampling technique. Data analysis used simple linear regression and multiple regression with the help of SPSS, as well as classical assumption tests to ensure the feasibility of the research model. The results of the study show that the leadership of madrasah heads has a positive and significant effect on teacher performance, as well as a significant effect on the quality of learning. In addition, teacher performance has been proven to play a role as a partial mediation variable in strengthening the influence of madrasah head leadership on learning quality. The value of the determination coefficient (R²) of 0.682 shows that 68.2% of the variation in learning quality can be explained by the leadership of the madrasah head and the teacher's performance. These findings confirm that improving the quality of learning cannot be separated from the strategic leadership role of madrasah heads who work through improving teacher performance. Conceptually, educational leadership serves as a transformational factor in building an effective learning ecosystem. The implications of this study show the importance of strengthening the leadership of madrasah heads based on managerial and Islamic education values to improve the quality of basic education in a sustainable manner.